2003
DOI: 10.1007/s00427-003-0364-2
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of neural stem cell markers suggests the occurrence of dedifferentiation in regenerating spinal cord

Abstract: Following tail amputation in urodele amphibians, an ependymal tube, that resembles a developing neural tube, forms from ependymal cells that migrate from the cord stump and elongates by cell proliferation. Expression of the keratin pair 8 and 18 has been observed in the developing urodele nervous system and is maintained in the ependymal cells of the mature cord. We show here that expression of these keratins is not unique to urodeles, but is also observed in the radial glia of the human spinal cord, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…The latter cell type often displays radial glia morphology and GFAP expression, and re-expresses the NSC markers vimentin and nestin upon amputation. (102) While de-differentiation has been generally considered a hallmark of amphibians (and fishes), it has regained interest since mammalian cortical astrocytes were shown to re-express BLBP around apoptotic lesions inducing neuronal regeneration. (85,86) To date, regeneration events have mostly been studied in different CNS structures in the different species (cerebellum and retina in teleosts, spinal cord in regenerative amphibians, telencephalon in the mouse), and the results above prompt a more systematic comparison to define real similarities and differences between species.…”
Section: Cell-intrinsic Mechanismsmentioning
confidence: 99%
“…The latter cell type often displays radial glia morphology and GFAP expression, and re-expresses the NSC markers vimentin and nestin upon amputation. (102) While de-differentiation has been generally considered a hallmark of amphibians (and fishes), it has regained interest since mammalian cortical astrocytes were shown to re-express BLBP around apoptotic lesions inducing neuronal regeneration. (85,86) To date, regeneration events have mostly been studied in different CNS structures in the different species (cerebellum and retina in teleosts, spinal cord in regenerative amphibians, telencephalon in the mouse), and the results above prompt a more systematic comparison to define real similarities and differences between species.…”
Section: Cell-intrinsic Mechanismsmentioning
confidence: 99%
“…Because most of the established experimental animals of developmental biology, such as mice, Drosophila, and Caenorhabditis elegans, have poor regenerative ability, there are not many comparative studies of regeneration and embryonic development. However, recent analyses have revealed that many genes that play a role in embryogenesis are re-expressed during regeneration (hydra: Technau and Bode, 1999;planarian: Baguñà , 1998;annelid: Bely and Wray, 2001;zebrafish: Akimenko et al, 1995;Monnot et al, 1999;amphibian: Gardiner et al, 1995;Mullen et al, 1996;Carlson et al, 1998Carlson et al, , 2001Koshiba et al, 1998;Torok et al, 1998;Khan et al, 2002;Beck et al, 2003;Walder et al, 2003;mouse: Han et al, 2003). This finding is consistent with the essential similarity between regeneration and embryogenesis with regard to involvement of cell differentiation and pattern formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, after tail amputation, the ependymal tube, which resembles a developing neural tube, expresses neural stem cell markers that are undetectable in a normal urodele spinal cord. This up-regulation of neural stem cell markers suggests the occurrence of a dedifferentiation process in the spinal cord in response to injury (Walder et al 2003). The same process is also found in the regeneration of the salamander jaw (Ghosh et al 1994).…”
Section: Dedifferentiation In Amphibiansmentioning
confidence: 79%